PENGEMBANGAN DESA WISATA BERKONSEP KAPASITAS INOVASI DAERAH DI DESA TANJUNGJAYA, KABUPATEN PANDEGLANG, PROVINSI BANTEN - Santoso, Sugeng; Pradipta, Syafaat; Sumantono, Trubus; Fatmawati, Ari Ana (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
Tanjungjaya Village is one of the villages located around the Tanjung Lesung Special Economic Zone (SEZ), Banten Province. The potential possessed by Tanjungjaya Village is tourism and the creative economy. The purpose of this study is to develop a tourism village model based on Regional Innovation Capacity which is expected to contribute to tourism village development and management policies. Regional Innovation Capacity (KID) was developed from the theory of National Innovation Capacity (KIN). KID approach by adjusting several variables to regional factors, developing industrial clusters, developing production function ideas, and regional strategic policies, especially related to tourism and the creative economy. The survey was conducted on respondents consisting of policymakers, tourist attractions managers, management partners, visitors, and creative economy actors. Data processing is done by exponential regression. The innovation-based tourism village model was developed with KID as the Y variable and the X variable consisting of 33 variables: 15 Innovation General Infrastructure variables, 13 Industrial Cluster variables, and 5 variables of Relationship between Innovation Public Infrastructure and Industrial Clusters. The 33 variables of X together affect KID and can predict KID by 72.4% (R Square adjusted value). The results of partial exponential regression processing with a significance of 5% indicate that: (i) KID will increase by e^.358 = 1.43 on the X1.7 variable (proportion of the number of regional sons who work in their region compared to those from outside the region) due to the percentage change in X1.7 of 35.8%; (ii) KID will increase by e^.368 = 1.44 in the X2.13 variable (number of industries that use the same infrastructure and resources in the creative and tourism industry clusters) due to the percentage change in X2.13 of 36.8%.